Characterization of trabecular bone density with ultra‐short echo‐time MRI at 1.5, 3.0 and 7.0 T – comparison with micro‐computed tomography. (4th August 2014) - Wurnig, Moritz C.; Calcagni, Maurizio; Kenkel, David; Vich, Magdalena; Weiger, Markus; Andreisek, Gustav; Wehrli, Felix W.; Boss, Andreas
<x xml:space="preserve">Abstract</x> The goal of this study was to test the potential of ultra‐short echo‐time (UTE) MRI at 1.5, 3.0 and 7.0 T for depiction of trabecular bone structure (of the wrist bones), to evaluate whether T2* relaxation times of bone water and parametric maps of T2* of trabecular bone could be obtained at all three field strengths, and to compare the T2* relaxation times with structural parameters obtained from micro‐computed tomography (micro‐CT) as a reference standard. Ex vivo carpal bones of six wrists were excised en bloc and underwent MRI at 1.5, 3.0 and 7.0 T in a whole‐body MR imager using the head coil. A three‐dimensional radial fat‐suppressed UTE sequence was applied with subsequent acquisitions, with six different echo times TE of 150, 300, 600, 1200, 3500 and 7000 µs. The T2* relaxation time and pixel‐wise computed T2* parametric maps were compared with a micro‐computed‐tomography reference standard providing trabecular bone structural parameters including porosity (defined as the bone‐free fraction within a region of interest), trabecular thickness, trabecular separation, trabecular number and fractal dimension (Dk). T2* relaxation curves and parametric maps could be computed from datasets acquired at all field strengths. Mean T2* relaxation times of trabecular bone were 4580 ± 1040 µs at 1.5 T, 2420 ± 560 µs at 3.0 T and 1220 ± 300 µs at 7.0 T, when averaged over all carpal bones. A positive correlation of T2* with trabecular bone porosity and trabecular separation, and a negative correlation of T2* relaxation time with trabecular thickness, trabecular number and fractal dimension, was detected (p < 0.01 for all field strengths and micro‐CT parameters). We conclude that UTE MRI may be useful to characterize the structure of trabecular bone, comparable to micro‐CT. Copyright © 2014 John Wiley & Sons, Ltd.